The Influence of Consumption Patterns, Nutritional Status, and Family Characteristics on Learning Achievement of Children at SD Inpres Mokdale in Rote Ndao District - Evelyn A. P. Iskandar; Stefanus P. Manongga; Helga J. N. Ndun (Lontar : Journal of Community Health, 2021)
One indicator of an individual's wellbeing is related to the nutritional status. The status is influenced by consumption patterns that can be determined by family conditions. Good nutritional status has a positive impact on learning achievement. The purpose of this study is to find whether there is a link between consumption pattern, nutritional status, and family characteristics on academic achievement. This research used an analytical survey method with a cross-sectional study design. The sample consisted of 118 children in grades 4 and 5 at SD Inpres Mokdale, Rote Ndao District, East Nusa Tenggara. Data analysis used the chi-square test with α=0,05. The results showed that there was no influence between parental education, parental work, family size and expenses on students' learning achievement. Consumption patterns and nutritional status also had no influence on the achievement. This research suggested that learning achievement can be influenced by other factors besides biological and family factors such as psychological factors, school environment, and the community support around the children.